2006
DOI: 10.4049/jimmunol.176.11.6879
|View full text |Cite
|
Sign up to set email alerts
|

Development and Selection of Edited B Cells in B6.56R Mice

Abstract: Tolerance to dsDNA is broken in mice with a high-affinity anti-DNA H chain transgene, 56R, on the C57BL/6 background (B6.56R). B6.56R produce more anti-dsDNA Abs than BALBc.56R. To investigate how anti-DNA Abs are regulated on the B6 background, phenotypic and genetic studies were performed. B6.56R have reduced numbers of B cells and phenotypically altered B cell subsets, including relative increases in the proportions of IgM-negative bone marrow B cells, cells with a marginal zone phenotype, and cells with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
95
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(110 citation statements)
references
References 56 publications
14
95
1
Order By: Relevance
“…Overrepresentation of T3 splenic B cells has also been observed in transgenic B6.56R mice (85) and in two other Ig-transgenic models with autoreactive B cells (20,86). In the latter two models, anti-Ars/A1 and anti-HEL/sHEL-transgenic mice, maintenance of the T3 phenotype was found to depend on continuous exposure to self-Ag.…”
Section: Autoreactive T3 Splenic B Cellsmentioning
confidence: 77%
“…Overrepresentation of T3 splenic B cells has also been observed in transgenic B6.56R mice (85) and in two other Ig-transgenic models with autoreactive B cells (20,86). In the latter two models, anti-Ars/A1 and anti-HEL/sHEL-transgenic mice, maintenance of the T3 phenotype was found to depend on continuous exposure to self-Ag.…”
Section: Autoreactive T3 Splenic B Cellsmentioning
confidence: 77%
“…Previous studies demonstrated that dsDNA specificity and differentiation into Ab-producing cells of 56R + B cells depend on the background genomes (13,14); B6.56R mice spontaneously produce both IgM and IgG anti-dsDNA Abs, whereas BALB/c.56R mice exhibit enhanced levels of IgM anti-dsDNA Abs compared with those in wild-type mice but lower levels than those in B6.56R mice. In particular, lupus-prone MRL/lpr.56R mice produce 20-fold more IgG-type Abs than do B6.56R mice (14).…”
Section: S Ystemic Lupus Erythematosus (Sle; or Lupus) Is A Chronicmentioning
confidence: 99%
“…B6.Sle1 mice, bearing NZM2410-derived lupussusceptibility intervals, were described previously (19). B6.56R mice were 56R anti-DNA HC KI mice, and the heterozygous mice have two HC alleles differentiated by using anti-allotype Abs: anti-IgM a binds Abs expressed by the 56R allele, and anti-IgM b binds Abs expressed by the endogenous allele (14,15). These transgenic mice were kind gifts from Dr. Martin Weigert (University of Chicago, Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations